Corporate Governance as a Moderating Variable for Identifying the Relationship Between CSR and Earnings Management : A Study of Listed Indian Mining Firms - Patro, Binoti; Pattanayak, J. K. (Prabandhan: Indian Journal of Management, 2017)
The purpose of this paper was to investigate the connection between earnings management and corporate social responsibility (CSR) for all the listed mining firms in India. This paper is an empirical work that used a sample of 40 listed mining firms in NSE/ BSE India for the period from 2007-2015. We found a positive impact of CSR disclosure on earnings management (EM) practices. We explained this result empirically by incorporating corporate governance and financial performance indicators for our proposed hypotheses. Investors and policy makers might be interested in the evidence on the not so good impact of governance on the relationship between CSR and EM. Tax authorities and audit committees might scrutinize whether there is implementation of Companies Act, 2013 by the mining companies. The companies which are not adopting the Act should be penalized accordingly. This paper is the first study of Indian mining firms that explored the relationship existing between CSR and earnings management by depicting the influences of Indian corporate laws in such a capital intensive industry.